Mechanical response of fiber reinforced concrete overlays over asphalt concrete substrate: Experimental results and numerical simulation - Isla Calderón, Facundo Andrés (2015)
Fiber reinforced concrete overlays are nowadays an alternative for repairing and reinforcing pavements. The contribution of concrete overlays strongly depends on the bond with the substrate. The fibers help sewing contraction joints and eventual cracks and, in this way prevent the propagation of cracks along the substrate-overlay interface. Therefore, the addition of fibers to the overlay allows reducing repair thickness, increasing service life and improving pavements general performance. Some experimental tests performed for the development of a method to assess different fibers efficiency in this type of applications are presented in this paper. Substrate-overlay composite beams are tested under flexure. The beams consist of overlays of plain and fiber reinforced concretes, containing steel and macro-synthetic fibers, applied over an asphalt concrete substrate. The numerical simulation of the beams is also included in the paper. Fiber reinforced concrete is considered as a composite material made of a concrete matrix and fibers and its mechanical behavior is modeled with a simple homogenization approach based on modified mixture theory. The numerical simulation can accurately reproduce material characterization tests and predict the bearing capacity of the composite beams. Furthermore, other substrate/overlay alternatives are numerically studied. The numerical results could be useful to improve the design of these intervention techniques.